Stakeholder Management in Developing a Sustainable Tourism Village Based on Renewable Energy Using RACI Matrix - Ma'arif, Syamsul; Putrianti, Flora Grace; Indraswari, Nurul Myristica; Nhu, Dương Quế; Pujianingsih, Esti Dwi; Marsinta, Ana Kardiya; Ardianti, Pipit (PT. SAFARI AMALIA, 2023)
The tourism village offers cultural, natural, and authentic culinary experiences, but the growth of tourism villages must be managed sustainably to address adverse environmental impacts. Stakeholder management becomes a critical factor in planning a sustainable energy-based tourism village development project. This research aims to identify key stakeholders in the development project of the